HUBUNGAN IKLIM KELAS TERHADAP MOTIVASI BELAJAR SISWA SMK ABDURRAB - Nasution, Itto Nesyia; Syaf, Auliya (Psychopolytan (Jurnal Psikologi), 2018)
This study aims to know the relationship between classroom climate with motivation to learn in Abdurrab Vocational School students Pekanbaru. The hyphothesis f this study is that there is a positive relationship between classroom climate with motivation to learn in Abdurrab Vocational School students Pekanbaru. Positive relationship indicates that the higher the classroom climate, the higher the motivation to learn. Conversely, the lower the classroom climate, the lower the motivation to learn. Subjects in this study 56 students of class X, class XI, class XII Abdurrab Vocational School Pekanbaru. The method used in this study is quantitative method in which consist of two scales, classroom climate scale which is based on the theory of classroom climate of McBer (Versha & Nicholls, 2003) and a motivation to learn scale is based on the theory of the motivation to learn of Uno (2009). The method of data analysis in this study using SPSS Statistic 10 with the technique of Pearson Product Moment Correlation. The result of data analysis showed r = 0.470 and p = 0.000 (p < 0.05). Studies show a positive relationship between classroom climate with motivation to learn in Abdurrab Vocational School students Pekanbaru, so the research hyphotesis is accepted.    Keywords:  classroom climate, motivation to learn